The Concept of Moral Progress - Albersmeier, Frauke (Practical Philosophy, 2022)
What is moral progress? Are we striving for moral progress when we seek to "make the world a better place"? What connects the different ways in which moral agents, their actions, and the world can become morally better? This book proposes an explication of the abstract concept of moral progress and explores its relation to our moral lives.